노인장기요양보험제도의 문제점 및 개선방안에 관한 고찰 - 안명선(Myung-Sun Ahn); 박주현(Joo-Hyun Park) (한국콘텐츠학회 논문지, 19(8), 2019)
Korea is facing one of the fastest aging population problems in the world due to the extension of life expectancy and low birth rates due to economic development and the development of health care. It has become difficult to take care of elderly people in need of long-term care at home, and social problems such as dementia and the increase in stroke cases are serious problems. The government is enacting and implementing the Long-Term Care Insurance Act for the purpose of improving the quality of life for senior citizens subject to long-term care and alleviating the burden of family support in order to solve such social structure and problems for senior citizens. However, as a result of the implementation of the long-term care insurance system for the elderly, the privatization of the facilities and the disorder are causing widespread requests for public accountability of the services and the enhancement of the quality of the facilities. In addition, various arrangements are needed for the production of low-wage medical care workers, tasks for quality improvement, problems regarding financing methods, and so on. In order to maintain and develop the long-term care insurance system for the elderly, the government will consider seeking ways to improve the legal and institutional aspects according to changes in the social environment of the age, as well as seeking mental and psychological measures for the stabilization of old life as well as physical health. 우리나라는 경제발전과 보건의료의 발달로 인한 평균수명의 연장과 저출산 등으로 세계에서 가장 급속도로 인구구조의 고령화 문제에 직면하고 있다. 정부는 이러한 사회적 구조 및 노인문제를 해결하기 위하여 장기요양대상 노인의 삶의 질 향상과 가족부양 부담의 완화 등을 목적으로 노인장기요양보험법을 제정 시행 중에 있다. 하지만, 노인장기요양보험제도의 시행결과, 시설의 민영화와 난립으로 서비스의 공적 책임과 시설의 질 제고에 대한 요청이 확산되고 있다. 이 밖에, 저임금 요양인력의 양산, 질 개선에 관한 과제, 재원조달 방식에 관한 문제, 등의 대비가 다각도로 필요하다. 이에 노인장기요양보험제도가 장기 지속적으로 유지 발전하기 위해서는 시대적인 사회환경의 변화에 따라 법 제도적 측면의 개선방안의 모색과 더불어 노인복지서비스가 신체적 건강뿐만 아니라 노후 생활의 안정을 위한 정신적 심리적 조치를 강구하는 방안을 검토한다.